A NEW OLIGO-MIOCENE MAMMAL-BEARING SITE FROM A SEDIMENTARY INTERCALATION IN THE TRAP BASALTS OF CENTRAL ERITREA. (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
We report the findings of two proboscideans from a sedimentary intercalation within the Central Eritrea Tertiary Trap basalt succession. These intertrappean sediments can be traced continuously between Tera’emni and Adi Quala in the Mendefera region, and are interbedded between the underlying Asmara/Aiba-Alaji basalts and the overlying Adi Ugri basalt. This intercalation is up to 50 m thick and consists of a predominant intensely pedogenized red, green and gray mudstone and siltstone with subordinate channelized pebbly sandstone. The newly discovered mammal remains come from the coarse-grained deposits in the Mai Gobro section.  Available radiometric datings of the host volcanic rocks constrain the age of the fossils between 24.6 and 22.1 Ma, i.e. at the transition between the Oligocene and the Miocene. The fossil vertebrate remains from Mai Gobro represent two proboscidean families, Deinotheriidae and Gomphotheriidae. The morphological grade of the two Mai Gobro proboscideans would suggest a more derived stage than that of representatives of the same families known from other Oligocene African sited (e.g. Chilga, Ethiopia), suggesting a possible Oligo-Miocene age.
Keywords: Afrotheria; Proboscidea; Oligo-Miocene; intertrappean sediments; Central Eritrea